Síntese e avaliação catalítica das zeólitas com estrutura BEA, MFI e MTW na reação de Knoevenagel - Chaves, Thiago Faheina (2014)
The use of zeolites in basic catalysis is small, especially when compared to the numerous applications of material in their acid form. Inside this context, are even smaller the number of studies on the use of as-synthesized zeolites as basic catalysts. Zeolites are crystalline hydrated aluminosilicates that have a pores size well-defined. Many of zeolite structures need organic compounds to be synthesized, these compounds are called structure directing agents. Zeolites containing organic cations (as-synthesized) have basic properties and can be used as catalysts in reactions that require this type of catalytic site. In this work were investigated three zeolites structures widely studied in the literature, BEA, MFI and MTW. Zeolites were synthesized with different compositions (ratio Si/Al) in the reaction mixture. Addition to the conventional synthesis were performed modifications using an organosilane (TPOAC - trimethoxysilyl-propyl-octadecylammonio chloride) in the synthesis of structures MFI and MTW. Were obtained, for the three structures, samples with different Si/Al ratios, some of them containing organosilane. The samples were characterized and used as catalysts in the Knoevenagel condensation. For all samples the increase of the Si/Al ratio increased the number of species [≡Si O ][TEA+]. The characterization and catalytic conversion show that for BEA zeolite only one portion of the species [≡Si O ][TEA+] were available for the reaction. The samples modified with organosilane (TPOAC) were the most active, especially with MTW structure. This increased activity is related to the modification that the organosilane promoted on the surface of the particles. The addition of organosilane favored the increase of the Si/Al ratio on the surface and this may be related to better conversion results. In this work, we propose new efficient catalysts, with zeolitic structure, for reactions involving basic sites.